Are submarine groundwater discharges affecting the structure and physiological status of rocky intertidal communities? - Piló, David (2018)
This study evaluated the impacts of submarine groundwater discharges (SGD) on a rocky intertidal community of South Portugal, during April-November 2011. Chlorophyll-a concentration was higher at the SGD site in respect to the Reference site. Epibenthic community structure differed between sites, with an increase in Chthamalus spp. and a decrease in macroalgae coverage at the SGD site. The abundance and body size of Mytilus galloprovincialis were consistently higher at the SGD site. During mid-spring, under potentially higher SGD and less favorable conditions for coastal phytoplankton, the ecophysiological condition of M. galloprovincialis and G. umbilicalis was also higher at the SGD site. These beneficial effects on filter-feeders and herbivores probably resulted from local increases in prey availability, supported by SGD-driven nutrient inputs. Conversely, P. depressa was not favoured by SGD, probably due to a lower dependency on algae as food. The analysis of epibenthic community structure and ecophysiological condition represents a promising approach to disentangle the ecological impacts of SGD on intertidal ecosystems.